Improving Water Introduction Learning Outcomes at SD Negeri Bubutan IV Surabaya Using Problem-Based Learning Model - Bagas Budi Cahya Kharisma; Bambang Ferianto Tjahyo Kuntjoro (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objectives. The primary objective of this research is to explore how the problem-based learning (PBL) model can be implemented to improve students' achievement in the basics of swimming and enhance their learning outcomes. Additionally, the research aims to investigate the impact of the performance method on students' motivation to learn the basics of swimming. By implementing PBL and performance methods, this research aims to provide a more engaging and effective learning experience for students, thus enhancing their achievement and proficiency in the basics of swimming., Materials and methods. This study aims to investigate the academic performance of fifth-grade students at SD Negeri Bubutan IV, Surabaya. The study employed an action research methodology, comprising two rounds, each consisting of two stages - design and implementation. The research seeks to address the challenges of low student engagement and proficiency in swimming, which can have negative impacts on their overall wellbeing. The research data was gathered from the results of tests, practices, observation sheets, and learning activities. The focus of this research is on reflection and revision to enhance the learning outcomes of the students.,. Results. The analysis results indicate that there was a significant increase in the learning achievement of students from cycle I to II. Specifically, there was a rise from 48.72% in cycle I to 87.18% in cycle II for the psychomotor domain. Similarly, there was a notable increase in the active domain, with cycle I recording 69.23% and cycle II recording 94.87% achievement. These findings suggest that the teaching approach implemented during the study was effective in enhancing students' learning outcomes. Conclusion. The findings of this research suggest that the demonstration method can have a positive impact on students' learning motivation. This is particularly true for students in Class V at Elementary School State Bubutan IV in Surabaya. Additionally, problem-based learning models can be used as an alternative teaching approach in Physical Education (PJOK). These results indicate that educators can benefit from using a combination of these methods to enhance student engagement and motivation in the classroom.